1983
DOI: 10.1007/bf00282711
|View full text |Cite
|
Sign up to set email alerts
|

A collaborative study of the measurement of glycosylated haemoglobin by several methods in seven laboratories in the United Kingdom

Abstract: A collaborative study compared methods for measuring glycosylated haemoglobin in seven laboratories in the United Kingdom. No satisfactory standard for general use was found. Satisfactory internal quality control systems were in use for each assay which allowed the maintenance of a normal range in each participating laboratory. No satisfactory quality control system suitable for general use could be identified. Costs and convenience of the assays are reported. The technical problems with each type of assay and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 16 publications
(11 reference statements)
1
13
0
Order By: Relevance
“…This finding constrasts with that described by Boucher et aJ. 11 who reported that this group produced the highest results and suggested that this may have been due to the Schiff base which they did not remove. In this present study, the Schiff base was removed by distributing red cells in saline, introducing an overnight incubation step whilst specimens were in the post.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This finding constrasts with that described by Boucher et aJ. 11 who reported that this group produced the highest results and suggested that this may have been due to the Schiff base which they did not remove. In this present study, the Schiff base was removed by distributing red cells in saline, introducing an overnight incubation step whilst specimens were in the post.…”
Section: Discussionsupporting
confidence: 80%
“…Precision (on distributed duplicate specimens) agrees with that previously reported. 11 Within-Iaboratory/between-batch precision usingfrozen haemolysates was poor for electroendosmosis and ion-exchange chromatography, mainly due to the instability of that type of specimen. Frozen haemolysates can therefore only be used to assess affinity chromatography methods.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 The disparate results obtained were because of the range of methods being used by laboratories, the lack of standardization, and lack of a primary reference material. Although the new generation of HbA 1c methods now demonstrate a degree of precision that could not be imagined 30 years ago, comparison of results from different laboratories would remain, at best, difficult -or, more likely, impossible -if not for standardization schemes.…”
Section: Standardization Of Hba 1c Analysismentioning
confidence: 99%
“…Following the introduction of HbA 1c methods into routine clinical practice around 1977, it quickly became apparent that there was a signifi cant difference in the results produced by different laboratories (8) with a between laboratory coeffi cient of variation (CV) of 11.2 % -20.1 % observed (9) . It was evident that the disparate results obtained were because of the range of methods being used by laboratories, the lack of standardisation and no primary reference material.…”
Section: The Need For Standardisationmentioning
confidence: 99%